(untitled) (INTI Nusa Mandiri, 2024)
The world of technology today greatly affects human life. Technological advances, especially in the field of information technology, are increasing every year. PT Sumber Jaya Maju Gemilang provides a variety of reinforced concrete products to meet the needs of different consumers for projects, factories, and other construction. During the sales process, it is still done manually, which hinders business because it takes a lot of time and causes errors in processing and reporting transaction data. Because of these problems, a new design for the Sales of Reinforced Concrete website must be designed using the design thinking method. The purpose of this study is to assist in creating sales applications that meet user needs and improve user experience. The results of the study show that the empathy stage, namely determining and observing previous cases, one of the problems that can be concluded from the empathize process is the company’s low level of awareness of their service users. In the previous stage, the idea was to create an application that could handle the problems of people who wanted to order iron and delivery of goods but did not have much time or did not want to queue for a long time. At this stage, the prototype must rearrange the flow of iron sales and delivery of goods so that it is easier, and create a pattern for creating features in the application. In the final stage, the application trial process is carried out using the digital prototype in the Figma Application.